Histopathologic Feature(s) of The Dactylogyrus sp-Infected Gills in The Ornamental Marine Fish - Putu Eka Sudaryatma; Ni Nyoman Eriawati (Jurnal Sain Veteriner, 2012)
In the present study, Dactylogyrus sp. was examined in the gill(s) of the ornamental marine fish due to the fact that this kind of parasite is very often found in those fishes without any pathognomonic clinical signs orpathologic anantomic lesions. The gill(s) samples collection and examination were performed in the Laboratory of Balai Karantina Ikan, Pengendalian Mutu dan Keamanan Hasil Perikanan. during Janury-July 2011. At first, the gills were examined natively and were subsequently processed for histopathologic examination. In the native examination, it was found the Dactylogyrus sp. with their size(s) ranging from 200-500 um. At necropsy, the gills were swollen and looked darker than normal. Based on the histopathologic lesions, the epithelial cells of the gills lamellas either primary or secondary became hyperplasia and fusion. The fusion of the gills is primarily thought to cause fatal to the fish due to significant oxygen depletion.Keywords: ornamental marine fish, gill, Dactylogyrus sp., native examination, hiperplasia and fusion.